Letter (copy) : Interntional Brigade Dependants and Wounded Aid Committee - Tewson, Vincent
034-0104-001 Substitute Secretary's. HVT/FC/EK/497. F.M.A.2. 23rd December, 1938. Mr. J. Marchbank, National Union of Railwaymen, Unity House, Euston Road, London, N.W.1. Dear Mr. Marchbank, International Brigade Dependants and Wounded Aid Committee. Your letter of the 13th December stating that your Executive felt that the appeal issued on behalf of the International Brigade should be endorsed and that it would be appropriate if the General Council of the Trades Union Congress were to make a direct appeal for funds through the Trade Union Movement, was placed before the General Council at their meeting this week. It is already known that several Unions are either rendering assistance to members who have been with the International Brigade or have contributed to their central fund. The General Council therefore decided that the previous decision taken on the question of assistance on behalf of the dependents and wounded members of the International Brigade, namely, "that in the circumstances no action could be taken on the lines proposed", should be adhered to. Wishing you the compliments of the Season. Yours sincerely, Assistant Secretary. 292/946/34/104